MENGINTEGRASIKAN NILAI ETIKA LINGKUNGAN DALAM AKUNTANSI : TINJAUAN FILSAFAT ILMU DAN IMPLIKASINYA BAGI KEBERLANJUTAN : - - Rahim, Nurhidayah; Habbe, Hamid; Pagalung, Gagaring (AkMen JURNAL ILMIAH, 2024)
This paper examines the importance of integrating environmental ethics values into accounting to support sustainability. In the context of rapid global economic development, the issues of natural resource exploitation and environmental degradation are increasingly urgent to address. The research methodology used is qualitative literature analysis focusing on traditional accounting practices and sustainability-oriented alternatives. The findings indicate that accounting needs to transform from a traditional shareholder-focused approach to a more holistic system that integrates ethical and environmental values. This approach is expected to motivate companies to make more responsible and sustainable business decisions. Thus, accounting is not only a reporting tool but also a catalyst for change towards an economy that respects environmental and social values.